Affirming identity, advancing belonging, and amplifying voice in sororities and fraternities - Sasso, Pietro A.; Miranda, Mónica Lee; Biddix, J. Patrick (Emerald Publishing Limited : Information Age Publishing, Inc., 2024)
"This text is a response to a call for existential exploration as an attempt to critically revivify our understanding of the sorority/fraternity experience as it contributes specifically to students' identity development and learning. The underpinning of the text centers the experiences of the student to amplify the student voice. Chapters in this text will attempt to foreground how the fraternity/sorority experience explicitly contributes to these areas of student development across multiple identities including race, ethnicity, culture, gender identity, social class, and ability. Authors will attempt to critically interrogate systems of oppressions that subjugate marginality from those with intersectional identities to recognize the larger challenges facing the sorority/fraternity movement as an attempt to disrupt these systems to better identify influences on identity development. This will be the first text to profile the spectrum of diversity that comprises the contemporary college student across sororities and fraternities. The volume will discuss student populations, trends, and issues in regard to how they are supported by our institutions. Furthermore, it will individually highlight the identity experiences of the diverse spectrum of fraternity and sorority members individually, collectively, and highlight the intersections of identity so often excluded from the literature to include, but not be limited to, college student challenges and crucial issues facing students within their organizations. The text will be grouped around centering their experiences through three A's: Amplifying Voice, Affirming Identity, and Advancing Belonging. Amplifying Voice will foreground marginalized social identities across student populations to explore how the sorority/fraternity experience expands their developmental narrative despite systemic barriers and personal challenges. Affirming Identity will center specific identities across gender, racial, and cultural identities to discuss how the sorority/fraternity uplifts their identity salience and may facilitate learning across differences. Advancing Belonging will highlight the potential ways in which the sorority/fraternity experience can involve student populations the research notes as "invisible identities" which are often pushed to the far boundaries of the co-curricular experience. Throughout this book, we invite students, their instructors, and other college/university practitioners to be mindful of the crucial, yet sometimes overlooked, connection between co-curricular campus activities and the academy's cardinal aim of learning, which often obscures a focus on identity or affective development. In the wake of the #AbolishGreekLife and other calls for racial justice, the role of identity development also becomes ever increasingly important as we consider how to make the sorority/fraternity more inclusive for our students. In the end, it may really be the power of inclusion on college campuses that leads to many of the educational goals that we yearn for in student growth: the formal and informal social interactions, bonded in reflective learning, that help build social and academic success. In this we can celebrate together, especially those of us who have savored so many "bright college years.""-- Provided by publisher.
Keywords: Greek letter societies -- Social aspects -- United States.; College fraternity members -- United States -- Social conditions.; College sorority members -- United States -- Social conditions.; Universities and colleges -- Sociological aspects.; Universities and colleges -- United States.; Education -- Student Life & Student Affairs.; Social groups: clubs and societies.; Educational administration and organization.; Student life.; elektronické knihy; electronic books